Training on Making Learning Videos with Open Broadcaster (OBS) for Muhammadiyah High School Teachers in Jakarta - Anita Dewi Ekawati; Sri Kusuma Ningsih; Silvie Mil (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Learning videos can be used as a learning tool. Learning videos have several advantages, including providing convenience in undergoing the learning process without being bound by space and time, and material can be repeated independently. Many learning videos can be accessed on social media. To facilitate learners in learning and attract their attention, learning videos must be made creatively and innovatively. One of the applications to create learning videos is Open Broadcaster Software (OBS). This community service uses the application to socialize to educators in the hope that educators can be helped in making interesting learning videos. Previously, OBS had never been used by educators in delivering material. This community service was attended by 40 Muhammadiyah high school teachers in Jakarta. On the first day of community service, the speaker explained about learning videos with OBS. On the second day, participants were asked to make their learning videos with the help of the community service team. Furthermore, participants presented the results of their work. Participants felt that it would be easier to convey material with learning videos and could be more creative with OBS.